2006
DOI: 10.1016/j.jtcvs.2006.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular diastolic filling patterns after coronary artery bypass graft surgery

Abstract: In patients with preoperative left ventricular diastolic dysfunction, biventricular filling patterns are impaired initially but return to preoperative status 6 months after coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 37 publications
1
39
2
2
Order By: Relevance
“…We have previously shown that hemodynamic instability after CPB is often the result of various mechanisms. 52 For instance, vasoplegia might not respond well to iMil; however, in patients undergoing coronary revascularization 33 and valvular and complex surgery, 32 RV dysfunction is almost invariably present after CPB. In this study, RV failure was present in more than one-third (13/36) of those patients with difficult or complex separation from CPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that hemodynamic instability after CPB is often the result of various mechanisms. 52 For instance, vasoplegia might not respond well to iMil; however, in patients undergoing coronary revascularization 33 and valvular and complex surgery, 32 RV dysfunction is almost invariably present after CPB. In this study, RV failure was present in more than one-third (13/36) of those patients with difficult or complex separation from CPB.…”
Section: Discussionmentioning
confidence: 99%
“…The examination included a midesophageal four-chamber view, a short-axis transgastric view at the mid-papillary level, and colour flow Doppler imaging of all the valves to detect any significant valvular disease. The RV function was evaluated using the fourchamber view with standard measurements, as previously described 33 and according to published guidelines. 34 The following measurements were obtained: right atrial transverse diameter (RADt), RV dimensions (at the annulus [RVD1], at the mid-portion [RVD2], and from the apex to the RV annular plane [RVD3]), the RV enddiastolic area (RVEDA), the RV end-systolic area (RVESA), the percentage of RV fractional area change (RVFAC) calculated as (RVEDA-RVESA)/RVEDA, and the tricuspid annular plane systolic excursion (TAPSE).…”
Section: Data Collectionmentioning
confidence: 99%
“…We have also previously reported the effects of anesthesia and surgery on diastolic function [26], but all the animals in the present study were submitted to the same degree of anesthesia. The systolic component of the pulmonary venous flow (S wave) has been shown to correlate well with LV filling pressure and with its change over time [27].…”
Section: Discussionmentioning
confidence: 99%
“…The latest echocardiography data from at least 6 months after the surgery were compared with preoperative echocardiography data. 10 We excluded 153 patients who had preoperative atrial fibrillation (n=26), more than grade 2/4 mitral regurgitation (n=46), undetermined diastolic function including sinus tachycardia (n=22), on-pump conversion (n=7), minimal invasive direct CABG (n=9), redo CABG (n=11), perioperative myocardial infarction (n=20), or an emergency operation (n=12). The remaining 1,101 patients who underwent elective isolated OPCAB were enrolled in this study, which was approved by the Institutional Review Board of Yonsei University College of Medicine.…”
Section: Study Populationmentioning
confidence: 99%
“…Usually, ventricular diastolic filling is impaired early after CABG, but improves approximately 6 months later. 10 To minimize this confounding factor, all of the postoperative echocardiography data in our study was from at least 6 months after the operation and before the occurrence of MACCE. Second, the patients with severe LVDD who still had severe LVDD postoperatively were classified in the non-aggravated group (group I).…”
Section: Study Limitationsmentioning
confidence: 99%